Immunization status of students of Nishtar medical university against hepatitis B - Khan, Dilawar; Shakeel, Hassan Abdullah; Maqsood, Hamza; Aziz, Hafiz Muhammad Ahmar; Qazi, Muhammad Jahantab; Shah, Syed Asfand Yar (International Journal of Research in Medical Sciences, 2018)
Background: Hepatitis B virus (HBV) infection causes significant morbidity and mortality worldwide. Occupational exposure of health care workers and medical students increase their risk of acquiring HBV infection, and many authorities recommend vaccination. However, significant proportions of health care workers do not receive HBV immunization, and remain at increased risk to HBV infection. The present study was conducted on medical students to evaluate their knowledge regarding HBV and to know their vaccination status. Methods: This cross sectional, randomized, observational study was done at Nishtar medical university, Multan from November 2017 to July 2018. A pre-structured and tested questionnaire was given to 150 medical students from first year to final year. Out of these students 75 were males and 75 were females. The students were also interviewed about age, gender, year of study, screening before vaccination, history of vaccination, completion of all 3 doses and reasons for not getting vaccinated. Results: Out of 150 participants, 117 (78%) were vaccinated against HBV. In the vaccinated group, 90 (77%) completed all the three doses of their vaccination schedule and remaining 27 (23%) students were incompletely vaccinated. Rate of vaccine uptake was higher in females; 63 (84%) than in males: 53 (71%). Reasons of not being vaccinated were lack of knowledge about consequences (15.5%), casual behaviour (36%), not knowing from where to get vaccine (12%), fear of injection (10%), busy in studies (10%) and financial problems (8%). Prior screening was done in 74 (63%) students before the vaccination. Conclusions: Despite the availability and accessibility of a cost-effective hepatitis B vaccine since mid80’s, the vaccination coverage among medical students is low. Health education needs to be improved in all medical students. The orientation and awareness programmes should be held to create awareness regarding HBV infection.